Virus-Gene Interactions in Amyotrophic Lateral Sclerosis and Ataxia with Oculomotor Apraxia - Surendran, Vithushan (My University, 2025)
Neurodegenerative disorders, including ataxia with oculomotor apraxia (AOA) and amyotrophic lateral sclerosis (ALS), are devastating diseases that lack effective treatments. Many genes have been associated with AOA and ALS, including mutations in SETX, TARDBP, and SOD1. However, there is considerable variability in the timing of onset and rate of progression of neurodegenerative disorders, even in patients with the same genetic mutation, which is attributed to environmental factors including viral infections. Moreover, the mechanisms through which viral infections influence the onset and progression of ALS remain poorly characterized. Common viral infections such as those caused by influenza viruses and coronaviruses induce immune responses which include antibody production through the SETX-dependent process of class switch recombination in B-cells. In addition, extracellular vesicles (EVs) have been demonstrated to be involved in the intercellular transmission of both viral proteins and genetic material as well as host genetic material and proteins including pathological SOD1 and TDP-43 Given the ubiquity of viral infections, it is essential to explore the relationship between viral infections, the immune response, and neurodegeneration. This dissertation describes cellular and murine models used to determine the relationship between neurodegenerative diseases, viral infections, and the immune system. We have observed virus-specific effects on both TDP-43 and SOD1 protein and mRNA expression intracellularly as well as their incorporation into EVs. Additionally, we have demonstrated that mutations in SETX result in a significant impairment in the class switching of antibodies to IgA and a reduction in IgA repertoire diversity. By exploring these interactions, we aim to enhance our understanding of how infections influence neurodegeneration, thereby informing the development of therapeutics to treat or prevent neurodegenerative diseases such as ALS and AOA.
VIRUS-GENE INTERACTIONS IN NEURODEGENERATIVE DISEASE
Keywords: Amyotrophic lateral sclerosis; Ataxia with oculomotor apraxia; Senataxin; TAR DNA binding protein; Superoxide dismutase; Influenza A virus; Coronavirus; Neurodegeneration; Viral infection